Technology Integration in Economic Education - Alhidayatullah, Alhidayatullah; Madhakomala, R. (International Journal of Social Science, Education, Communication and Economics, 2024)
The incorporation of technology in economic education yields numerous advantages, such as enhanced accessibility, more engaging instruction, and the cultivation of data analytic competencies pertinent to the professional realm. Numerous studies address the incorporation of technology in education; nevertheless, research focusing on the integration of technology in economic education remains few. This study is to examine and elucidate the use of technology in economic education. The employed research methodology was quantitative, utilizing a sample of 142 participants, comprising lecturers and students from the 3rd, 5th, and 7th semesters of the Faculty of Economics at the University of Muhammadiyah Sukabumi. The data gathering method is a questionnaire disseminated to participants via Google Forms, while the data analysis employs multiple linear regression. The study's results indicate a substantial favorable impact of technology integration in economic education, with an influence of 67%. This research contributes by providing references in education, particularly with the incorporation of technology in economics instruction.